Potential conformational heterogeneity of p53 bound to S100B(ββ) - McDowell, Chester; Chen, Jianlin; Chen, Jianhan (My University, 2013)
The negative regulatory domain (NRD) of the p53 tumor suppressor is intrinsically disordered. It contains several post-translational modification (PTM) sites that are important for regulation of p53 activity. Calcium-dependent binding of dimeric S100B(ββ) to p53-NRD blocks access to these PTM sites and disrupts the p53 tetramer to inhibit p53 activation. Previous NMR structural studies have suggested that p53-NRD folds into a stable helix upon binding to S100B(ββ). Intriguingly, despite the well-converged and stably folded nature of the NMR structure ensemble, experimentally resolved intermolecular NOEs are extremely weak; most have 5−6 Å upper bounds, and mainly involve the C-terminal segment of p53-NRD. Such a systematic lack of strong intermolecular NOEs could suggest that the p53/S100B(ββ) interface is more dynamic than currently believed. Indeed, extensive atomistic simulations in explicit solvent (with 1.0 μs total effective sampling) revealed large heterogeneity in the S100B(ββ)-bound conformation of p53-NRD. Helix unwinding at the C-terminus allows key hydrophobic residues (Leu383 and Phe385) to make more extensive intermolecular contacts, whereas the highly helical N-terminus displays substantial flexibility in packing with S100B(ββ). Importantly, the predicted heterogeneous ensemble as a whole is highly consistent with experimental intermolecular NOEs, although many conformational sub-states coexist and individual sub-states satisfy only subsets of the NOE restraints. Furthermore, the simulated ensemble provides similar shielding of key PTM sites to support p53 inhibition. This study not only provides new insights into the structural basis of the p53/S100B(ββ) recognition, but also highlights the importance of recognizing dynamic complexes in structural studies of IDP interactions.
Citation: McDowell, C., Chen, J., & Chen, J. (2013). Potential conformational heterogeneity of p53 bound to S100B(ββ). Journal of Molecular Biology, 425(6), 999- 1010.
Keywords: p53 tumor suppressor; S100B(ββ); Negative regulatory domain; Intrinsically disordered proteins